2015
DOI: 10.5604/20831862.1150305
|View full text |Cite
|
Sign up to set email alerts
|

Alternative to traditional stretching methods for flexibility enhancement in well-trained combat athletes: local vibration versus whole-body vibration

Abstract: This study aimed to compare the effect of local vibration (LV) and whole body vibration (WBV) on lower body flexibility and to assess whether vibration treatments were more effective than traditionally used static and dynamic stretching methods. Twenty-four well-trained male combat athletes (age: 22.7 ± 3.3 years) performed four exercise protocols – LV (30 Hz, 4 mm), WBV (30 Hz, 4 mm), static stretching (SS), and dynamic stretching (DS) – in four sessions of equal duration 48 hours apart in a randomized, balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 33 publications
0
39
1
3
Order By: Relevance
“…He compared the effect of local vibration (LV) and WBVE on lower body flexibility and to assess whether vibration treatments were more effective than traditionally used SS and DS methods. Kurt (2015) observed that there was a similar change pattern in S&R scores across the 15-minute recovery after each protocol (p = 0.572), remaining significantly elevated throughout recovery. A significant main protocol effect was found for absolute change in S&R scores relative to baseline (p = 0.015).…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…He compared the effect of local vibration (LV) and WBVE on lower body flexibility and to assess whether vibration treatments were more effective than traditionally used SS and DS methods. Kurt (2015) observed that there was a similar change pattern in S&R scores across the 15-minute recovery after each protocol (p = 0.572), remaining significantly elevated throughout recovery. A significant main protocol effect was found for absolute change in S&R scores relative to baseline (p = 0.015).…”
Section: Resultsmentioning
confidence: 65%
“…They have investigated the effect of WBVE training on maximal strength, squat jump, and flexibility of well-trained combat athletes. Kurt (2015) has assessed the static SS, and DS -in four sessions of equal duration 48 hours apart in a randomized balanced order. During a 15-minute recovery after each protocol, subjects performed the stand and reach test (S&R).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations